The RNA-Binding Motif Protein Family in Cancer: Friend or Foe? - Li, Zhigang; Guo, Qingyu; Zhang, Jiaxin; Fu, Zitong; Wang, Yifei; Wang, Tianzhen; Tang, Jing (Frontiers in Oncology, 2021)
The RNA-binding motif (RBM) proteins are a class of RNA-binding proteins named, containing RNA-recognition motifs (RRMs), RNA-binding domains, and ribonucleoprotein motifs. RBM proteins are involved in RNA metabolism, including splicing, transport, translation, and stability. Many studies have found that aberrant expression and dysregulated function of RBM proteins family members are closely related to the occurrence and development of cancers. This review summarizes the role of RBM proteins family genes in cancers, including their roles in cancer occurrence and cell proliferation, migration, and apoptosis. It is essential to understand the mechanisms of these proteins in tumorigenesis and development, and to identify new therapeutic targets and prognostic markers.